Auxotrophy and intrapopulation complementary in the ‘interactome’ of a cultivated freshwater model community - Sarahi L. Garcia; Moritz Buck; Katherine D. McMahon; Hans‐Peter Grossart; Alexander Eiler; Falk Warnecke (Molecular Ecology, 2015)
Microorganisms are usually studied either in highly complex natural communities or in isolation as monoclonal model populations that we manage to grow in the laboratory. Here, we uncover the biology of some of the most common and yet‐uncultured bacteria in freshwater environments using a mixed culture from Lake Grosse Fuchskuhle. From a single shotgun metagenome of a freshwater mixed culture of low complexity, we recovered four high‐quality metagenome‐assembled genomes ( MAG s) for metabolic reconstruction. This analysis revealed the metabolic interconnectedness and niche partitioning of these naturally dominant bacteria. In particular, vitamin‐ and amino acid biosynthetic pathways were distributed unequally with a member of Crenarchaeota most likely being the sole producer of vitamin B12 in the mixed culture. Using coverage‐based partitioning of the genes recovered from a single MAG intrapopulation metabolic complementarity was revealed pointing to ‘social’ interactions for the common good of populations dominating freshwater plankton. As such, our MAG s highlight the power of mixed cultures to extract naturally occurring ‘interactomes’ and to overcome our inability to isolate and grow the microbes dominating in nature.